An overview of Applications, Concepts, Challenges in 5G Technology - Srivastava, Vijay Kumar; Rav, Suman; Goel, Nitin (International Journal of Computer Sciences and Engineering, 2025)
This paper provides a comprehensive overview of advance wireless communication technology that is known as 5G. In 5G there are more advancement is happening towards the development of World Wide Wireless Web (WWWW), Dynamic Ad-hoc Wireless Networks (DAWN) and Real Time Wireless Communication. The most important technologies for 5G technologies are 802.11 and 802.16, Wireless Personal Area Network. 5G technology will include several standards under a common umbrella, similar to 4G. 5G technology is to make use of mobile phones within very high bandwidth. This paper is also trying to show the future of wireless system to the users of current 4G users.